EVALUASI PENGELOLAAN ANGGARAN PADA PUSAT PELATIHAN PROFESI PARIWISATA DAN EKONOMI KREATIF DKI JAKARTA - Annisa Nur Abdillah; Fujianti, Lailah; Damayanti, Ameilia (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2024)
The state budget is the official financial plan of the government. The goal is to regulate income and allocation of funds within a certain period of time. Budget management involves planning, allocating, supervising, and evaluating funds. It aims to increase efficiency and effectiveness, as well as achieve project or organizational goals. The purpose of this study is to evaluate budget management at the Tourism and Creative Economy Training Center, fiscal year 2019-2023. The research methods used in this study are descriptive qualitative with data collection techniques derived from literature studies, interviews and observations. The results of the study show that the budgeting procedure carried out by the Tourism and Creative Economy Professional Training Center has run well and also follows the regulations issued by the government, it also shows the financial performance of the Tourism and Creative Economy Professional Training Center in terms of its efficiency ratio can be said to be efficient with an average percentage of 77.69%.Keyword: Budget Management, Efficiency, Tourism Profession Training Center and Creative Economy